2019
DOI: 10.1186/s40623-019-1044-4
|View full text |Cite
|
Sign up to set email alerts
|

Cause of destructive strong ground motion within 1–2 s in Mukawa town during the 2018 Mw 6.6 Hokkaido eastern Iburi earthquake

Abstract: We investigated the cause of destructive ground motion during the 2018 Hokkaido eastern Iburi earthquake. We conducted strong motion observations of aftershocks and microtremors and the surface wave method in the damaged areas of the town of Mukawa, Hokkaido prefecture, Japan. The ground accelerations were continuously recorded during a period of approximately 3 months after the main shock on September 6, 2018. The heavily damaged buildings were mainly situated around the strong motion station (HKD126) in Muka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…This implies that this thick-mudstone-layer region in southern Taiwan plays a critical role in seismic hazards. A recent study by Takai et al (2019) also found that the cause of destructive ground motion, which had a predominant period of 1-2 s, during the 2018 Mw 6.6 Hokkaido eastern Iburi earthquake was nonlinear amplification by the shallow underground velocity structure. Thus, investigating the site effects of the mudstone layer in southern Taiwan is crucial because of its complex behavior and influence, and these factors should be considered to the application of seismic hazard mitigation.…”
Section: Discussionmentioning
confidence: 91%
“…This implies that this thick-mudstone-layer region in southern Taiwan plays a critical role in seismic hazards. A recent study by Takai et al (2019) also found that the cause of destructive ground motion, which had a predominant period of 1-2 s, during the 2018 Mw 6.6 Hokkaido eastern Iburi earthquake was nonlinear amplification by the shallow underground velocity structure. Thus, investigating the site effects of the mudstone layer in southern Taiwan is crucial because of its complex behavior and influence, and these factors should be considered to the application of seismic hazard mitigation.…”
Section: Discussionmentioning
confidence: 91%
“…The sudden energy release is supposed to have originated from a major slip along the faulting plane [7,8]. This subterranean slip then translated at the surface into strong motion, notably under the amplification of the near-subsurface structure [9]. The near-subsurface is made of +/−9000 years old air-fall lapilli-sized pumice soil layers (about 1.5 m thick).…”
Section: The 2018 Hokkaido Iburi-tobu (Hit) Earthquake and The Coseismic Mass-movementsmentioning
confidence: 99%
“…For the soil type of the alluvium, the layers of clay, gravel, and silt are alternated in Mukawa, according to the PS-logging information of K-NET (HKD126). In addition, it was reported that a non-linear ground response occurred at the earthquake observation point (HKD126) in Mukawa [11], which may be related to building damage. In the future, it will be necessary to study the nonlinear ground response based on the ground structure model obtained in this study and to clarify the factors causing the damage.…”
Section: S-wave Velocity Structuresmentioning
confidence: 99%